Restoration of posterior tooth with single shade composite: a case series - Muhamad Halil, Mohd Haikal; Abdul Shukur, Nur Dini; Abdul Hamid, Nor Salsabila Hanis; Kamaruzaman, Syahirah Aisyah (IIUM Press, 2022)
Composite restoration is a popular material to restore tooth structure due to dental caries as there is an increasing demand for aesthetic restoration. With the advancing technologies, it has excellent physical characteristics which increases its longevity. However, the appropriate case selection also influences the outcome as composite is technique sensitive. This material can be offered to patient seeking less time-consuming procedure, better preservation of tooth structure, affordable but acceptable aesthetic outcome. These three cases presented shows the possibility of creating a good aesthetic result in